(untitled) (Culturas Científicas, 2022)
Editorial made for the dossier ’Philosophy of Psychiatry’ by its guest editors Manuel Reyes Barraza and Fernando Ivanovic-Zuvic Ramírez. All published articles underwent regular double-blind peer review.